(3hGbYGJ GdeaJjfs - (3YHO GdbGOQ Hf jhSa bOQj CafOj, J (B1083 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hHYO ajbhd YHO GdbGQ Hf jhSa LeYJ CKfGA GdNOeI GdeSGFd GdhGbYI ef GdcJH GdeYJHQI hGdaJGhi hSejJgG HhGbYGJ GdeaJjf cJGH GdWgGQI GdeGA GdPj ojJhVC Hg KdGKIs
(3BNQgG (B:s
(3Ef hLH HYbOg UM YfOgeG hVef hdG jUM YfO GdKGfj hEf hLH dG dYbOg YfO Gdcd hCRjO aj fhY aj JUQaGJ GdCH hGdhUj ef cJGH GdhUGjGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 48s
(3eYLe GdeDdajf (B2 / 200s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdabg GdMfHdjs